1979
DOI: 10.1039/an9790401030
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of nanogram amounts of cadmium and other metals from aqueous solution using hexamethyleneammonium hexamethylenedithiocarbamate as the chelating agent

Abstract: A group of metals can be extracted from aqueous solution by using hexamethyleneammonium hexamethylenedithiocarbamate as the chelating agent and a mixture of 2,4-dimethylpentan-3-one and xylene as the organic phase. A description is given of a procedure for the determination of microgram and nanogram amounts of the nine metals silver, bismuth, cadmium, copper, nickel, lead, thallium and zinc in aqueous solution.The influence of a high content of iron and copper on the extraction is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Busev et al (17) reported the extraction of 14 heavy metals in chloroform but did not indicate the concentration of metals. Dornemann et al (18) also reported the extraction of HMDC chelates using methyl isobutyl ketone and diisopropyl ketone (DIBK) as organic solvents. The parts-per-billion levels of Cd, Ni, Zn, Co, Mn, Cu (10 ppb) and P b (40 ppb) have been reported by Tao et al (19).…”
Section: Resultsmentioning
confidence: 99%
“…Busev et al (17) reported the extraction of 14 heavy metals in chloroform but did not indicate the concentration of metals. Dornemann et al (18) also reported the extraction of HMDC chelates using methyl isobutyl ketone and diisopropyl ketone (DIBK) as organic solvents. The parts-per-billion levels of Cd, Ni, Zn, Co, Mn, Cu (10 ppb) and P b (40 ppb) have been reported by Tao et al (19).…”
Section: Resultsmentioning
confidence: 99%
“…The filtered samples were stored at 4~ in the dark until analysis. Dissolved Cd, Cu and Zn were determined in the clean laboratory by atomic absorption spectroscopy after preconcentration in HMDC-DIPK, following the method of DORNEMANN and KLEIST (1979).…”
Section: General Water Quality and Dissolved Trace Metalsmentioning
confidence: 99%
“…Different organic ligands have been used for extraction of metal ions into organic solvents: dithiocarbamates, quinolinoles, dithizone, etc. [8][9][10] For this system diethyldithiocarbamate (DDC) was chosen as the most suitable extraction agent due to its high binding affinity for many of the metals of interest, and theoretically allowing the metals to be extracted at a conveniently low solution pH, see results of calculations in electronic supplementary information{. The theoretical considerations reveal that under acid conditions with a pH of 0.3 the ratios between DDC complexed metal in a 4-methylpentan-2-one (methyl-isobutylketone, MIBK) phase and metal in an aqueous phase are several orders of magnitude lower than 1 for Fe and Mn and several orders of magnitudes higher than 1 for the metals Cd, Pb, Ag, Ni, Cu and Hg.…”
Section: Solvent Extraction Calculationsmentioning
confidence: 99%